2018
DOI: 10.1212/nxi.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response syndrome, infection, and outcome in intracerebral hemorrhage

Abstract: Objective:Systemic inflammatory response syndrome (SIRS) may be related to poor outcomes after intracerebral hemorrhage (ICH).Methods:The Ethnic/Racial Variations of Intracerebral Hemorrhage study is an observational study of ICH in whites, blacks, and Hispanics throughout the United Sates. SIRS was defined by standard criteria as 2 or more of the following on admission: (1) body temperature <36°C or >38°C, (2) heart rate >90 beats per minute, (3) respiratory rate >20 breaths per minute, or (4) white blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
(47 reference statements)
7
29
0
Order By: Relevance
“…From the GSE24265 dataset, after comparing the gene expression data obtained from ICH tissue with that obtained from the contralateral brain tissues, we obtained 67 DEGs. GO analysis indicated that the main functional annotation results were consistent with those obtained by previous reports, i.e., a significant increase in inflammatory response promotes ICH-induced brain injury, which may be one of the main factors contributing to the poor prognosis in patients with ICH (Boehme et al 2018;Fu et al 2018). The immune response can antagonize the inflammatory response, induced after an episode of cerebral hemorrhage, to reduce the secondary damage to brain tissue, and thereby improve the recovery of nerve function (Klebe et al 2015;Lu et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…From the GSE24265 dataset, after comparing the gene expression data obtained from ICH tissue with that obtained from the contralateral brain tissues, we obtained 67 DEGs. GO analysis indicated that the main functional annotation results were consistent with those obtained by previous reports, i.e., a significant increase in inflammatory response promotes ICH-induced brain injury, which may be one of the main factors contributing to the poor prognosis in patients with ICH (Boehme et al 2018;Fu et al 2018). The immune response can antagonize the inflammatory response, induced after an episode of cerebral hemorrhage, to reduce the secondary damage to brain tissue, and thereby improve the recovery of nerve function (Klebe et al 2015;Lu et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…vs 6, IQR[3][4][5][6][7][8][9][10][11][12]; p < 0.01; Glasgow Coma Scale score: 11, IQR[3][4][5][6][7][8][9][10][11][12][13][14] vs 15, IQR [13-15]; p < 0.01) and less favorable ICH characteristics (ICH volume: 18.3 cm 3 , IQR [4.6-47.2] vs 7.4 cm 3 , IQR [2.4-18.6]; p < 0.01; IVH: 57.6%, n = 98/170 vs 24.8%, n = 79/ 319; p < 0.01; hematoma enlargement: 12.7%, n = 15/118 vs 4.3%, n = 11/258; p < 0.01). Unadjusted outcomes comparing SIRS vs controls (at hospital discharge: mRS score 5, IQR [4-6] vs 3, IQR [2-5]; at 3 months: mRS score 5, IQR [3-6] vs 3, IQR [2-4]; at 12 months: mRS score 6, IQR [3-6] vs 3, IQR [1-5]; all p < 0.01) were all significantly in disfavor of patients with SIRS.…”
mentioning
confidence: 99%
“…In ICH, approximately 20% of patients develop SIRS during hospital stay, 2 and a correlation between SIRS and stroke severity has been suggested. 4 Recent stroke research has focused on systemic and local inflammatory responses as novel therapeutic target (NCT03338998), 3,5 yet the association of SIRS with functional long-term outcomes after ICH remains undetermined. The present study aimed at investigating associations of SIRS with long-term functional outcome and contributing factors after ICH.…”
mentioning
confidence: 99%
“…Zhao et al found that p38MAPK was activated at 24 h in an animal model of ICH, and the use of an inhibitor could recede the inflammatory injury after ICH (Zhou et al 2014 ). Boehme AK et al showed systemic inflammatory response syndrome (SIRS) on admission was associated with an ICH score on admission and infection after ICH infection (Boehme et al 2018 ). Together, MAPK/ERK and p38MAPK could represent potential therapeutic targets to prevent neurological deficits after ICH.…”
Section: Discussionmentioning
confidence: 99%